Nonconserved tryptophan 38 of the cell surface receptor for subgroup J avian leukosis virus discriminates sensitive from resistant avian species - Kucerová, Dana; Plachy, Jirí; Reinisová, Markéta; Senigl, Filip; Trejbalová, Katerina; Geryk, Josef; Hejnar, Jirí (Journal of virology, 2013)
Subgroup J avian leukosis virus (ALV-J) is unique among the avian sarcoma and leukosis viruses in using the multimembrane-spanning cell surface protein Na(+)/H(+) exchanger type 1 (NHE1) as a receptor. The precise localization of amino acids critical for NHE1 receptor activity is key in understanding the virus-receptor interaction and potential interference with virus entry. Because no resistant chicken lines have been described until now, we compared the NHE1 amino acid sequences from permissive and resistant galliform species. In all resistant species, the deletion or substitution of W38 within the first extracellular loop was observed either alone or in the presence of other incidental amino acid changes. Using the ectopic expression of wild-type or mutated chicken NHE1 in resistant cells and infection with a reporter recombinant retrovirus of subgroup J specificity, we studied the effect of individual mutations on the NHE1 receptor capacity. We suggest that the absence of W38 abrogates binding of the subgroup J envelope glycoprotein to ALV-J-resistant cells. Altogether, we describe the functional importance of W38 for virus entry and conclude that natural polymorphisms in NHE1 can be a source of host resistance to ALV-J.
Keywords: Virus Internalization; tropismus virů; tryptofan; Receptors, Virus; virové receptory; DNA Mutational Analysis; Sodium-Hydrogen Exchangers; Animals; Viral Tropism; ptáci; Birds; Na(+)-H(+) antiport; Tryptophan; internalizace viru; zvířata; virus ptačí leukózy; Avian Leukosis Virus; mutační analýza DNA